Preliminary Study of Distribution of Soil Available Nutrients in Loquat (Eriobotrya japonica) Orchards and Their Responses to Environmental Factors Based on Path Analysis Model - Yue Zhao; Linzhong Gong; Furong Wang; Yong Liu; Xiaoyan Ai; Wei Zhu; Yang Zhang; Zhimeng Gan; Huaping He; Huiliang Wang (Agronomy)
Soil available nutrients (SANs) can be rapidly converted, absorbed, and utilized by crops. The study of the spatial distribution and variation of SANs, as well as their response to environmental factors, is crucial for precision fertilization and soil ecosystem function regulation. In this study, 220 soil surface-layer samples (0–20 cm) were collected in 2019 from loquat orchards in the mid-low mountain hilly areas of central China to explore the spatial distribution and variation of SANs, as well as the effects of environmental factors (including the topography, vegetation index, soil property, and climate) on SANs, using a path analysis model. The results showed that the available potassium (AK) and ammonium nitrogen (AN) levels exhibited a moderate average content, which was 123.14 mg·kg−1 and 119.03 mg·kg−1, respectively, whereas available phosphorus (AP) levels displayed a high average content (26.78 mg·kg−1), and all three SANs showed an uneven spatial distributions. The nugget effect values of AK and AN ranged from 25% to 75%, indicating moderate spatial variation, and those of AP were <25%, suggesting high spatial variation. Furthermore, the mean annual precipitation (MAP) had a direct positive effect on AK levels, while slope had an indirect effect on AK levels through the ratio vegetation index (RVI), suggesting that precipitation had greater impact on AK levels than topography. Soil erosion had a direct negative effect on AP and AN levels, accelerating the loss of SANs. The MAP and soil type (ST) directly affected soil AN content. Specifically, sufficient precipitation and fine soil facilitated the storage and conversion of AN in soil. Taken together, our path analysis indicated that all the four categories of environmental factors had direct or indirect effects on SANs, and our geostatistical analysis revealed the spatial distribution and variation law of SANs in the study area. Our findings offer a theoretical basis and valuable references for achieving precision fertilization in orchards and improving loquat yield and quality.